2021
DOI: 10.1007/s00464-021-08678-6
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a preoperative “difficulty score” for laparoscopic transabdominal adrenalectomy: a multicenter retrospective study

Abstract: Background A difficulty score for laparoscopic adrenalectomy (LA) is lacking in the literature. A retrospective cohort study was designed to develop a preoperative “difficulty score” for LA. Methods A multicenter study was conducted involving four Italian tertiary centers for adrenal disease. The population was randomly divided into two subsets: training group and validation one. A multicenter study was undertaken, including 964 patients. Patient, adrenal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 35 publications
(34 reference statements)
2
15
0
Order By: Relevance
“…As another factor, while BMI is used to evaluate degree of obesity, it primarily reflects body fat composition, and the distribution of visceral fat, especially perirenal fat, may differ. Therefore, the prediction of BMI on difficulty of RPLA is still controversial, with a limited number of studies suggesting that BMI has a significant impact (1,14,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As another factor, while BMI is used to evaluate degree of obesity, it primarily reflects body fat composition, and the distribution of visceral fat, especially perirenal fat, may differ. Therefore, the prediction of BMI on difficulty of RPLA is still controversial, with a limited number of studies suggesting that BMI has a significant impact (1,14,21).…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic surgery is further divided into transperitoneal laparoscopic adrenalectomy (TPLA) and retroperitoneal laparoscopic adrenalectomy (RPLA), with TLPA first competed in 1992 by Gagner et al (9) and Higashihara et al (10) and RPLA first proposed by Gaur et al (11), later refined by Walz et al (12). Compared with TLPA, RPLA has less postoperative pain, fewer complications, and lower incidence of intraoperative adverse events such as hemodynamic instability and massive bleeding (13,14). However, there is currently no effective evaluation system for the difficulties of RPLA.…”
Section: Introductionmentioning
confidence: 99%
“…Creation of such a scoring system would help to guide the selection of surgical methods and predicting the difficulty of surgery. In 2021, Alberici et al devised a scoring method that could be used to predict the difficulty of transabdominal laparoscopic adrenalectomy using three models and found that this score could also predict a complicated postoperative course [ 7 ]. Furthermore, Vrielinkom et al reported that retroperitoneal laparoscopic adrenalectomy could reduce the operating time, amount of blood loss, and complication rate in comparison with transabdominal laparoscopic adrenalectomy [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…7,19,20 Adrenal mass size represents one of the major factors in the selection of the surgical approach, and a predictor of difficulty, conversion, and complications. 15,[21][22][23][24] Previous reports suggested that the cutoff for performing a minimal invasive approach is <6 cm due to the increased risk of malignancy. 4,13,[25][26][27] More recent reports on the feasibility and safety of performing larger size masses up to 12 cm, [27][28][29][30][31] especially in the era of robotic surgery, with growing evidence to support its safety.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenal mass size represents one of the major factors in the selection of the surgical approach, and a predictor of difficulty, conversion, and complications 15,21–24. Previous reports suggested that the cutoff for performing a minimal invasive approach is <6 cm due to the increased risk of malignancy 4,13,25–27.…”
Section: Discussionmentioning
confidence: 99%